Macrofauna associated with intertidal mussel beds in the Knysna estuarine embayment, South Africa. Issue 1 (2nd January 2021) - Hodgson, Alan N; Smith, Frances; Smith, Peter; Claassens, Louw
Abstract : The alien invasive mussel, Mytilus galloprovincialis, forms biogenic habitats in the embayment of Knysna Estuary. Invertebrate macrofauna inhabiting mussel beds were sampled from six sites in the embayment. In addition, mussel cover, mussel bed depth, density and size of mussels were recorded. With the exception of two sites (The Heads and Featherbed) where some Perna perna was present, we confirmed that the mussel beds were composed of the invasive species M. galloprovincialis . At The Heads, mussel beds were single-layered and in patches, whereas at other sites they were multi-layered with 100% cover. Bed depth, mussel density and shell size varied among sites. A total of 65 taxa (mainly Crustacea and Mollusca) were identified across all sites with species richness and diversity being significantly different among sites. Forty-three percent of taxa were new records for the estuary. Macrofaunal richness and diversity were highest at the two sites (The Heads and Featherbed) closest to the mouth of the embayment. There were negative relationships between species diversity and mussel density, and diversity and macroinvertebrate abundance. At most sites macrofaunal abundance was dominated by one or two species. Multivariate analysis revealed a significant difference in species composition among sites. Where wave action was present (The Heads, Featherbed and Leisure Isle) only a few deposit feeders were present in the mussel beds. At sites where wave action was minimal (Thesen Wharf, Marina and Railway Bridge) fine silt was present in the mussel matrix and there was an increase in the number of deposit feeding species.